KAMUS ISTILAH MEDIS BERBASIS WEB MENGGUNAKAN PHP - Citra Mahardika, Alifia; , Husni Thamrin, S.T., M.T.,Ph.D (2016)
Understanding a health worker in understanding the meaning of the terms health is very important to support the knowledge in knowing the person's condition and can improve its performance as a health worker. Comprehension about the meaning of a term can be helped by the presence of dictionary terms. This web-based dictionary is designed to help learners study the medical profession and ordinary people who want to understand the terms or abbreviations used in the medical profession. Existing medical dictionary currently there are only devoted to the term in English or just a long table so that the search process is still less effective. Designing dictionary medical terms it uses the model of UML (United Modeling Language ). Line diagrams depicted in use-case diagrams and activity diagrams. Design Dictionary of Terms This web based programming language PHP and MYSQL database. Data were obtained from medical books. Results obtained in the form of a dictionary term web-based application that allows users to search terms with the word just typing a keyword in the form provided without the need to find one by one word that takes a long time.